2009
DOI: 10.1007/s00442-009-1307-z
|View full text |Cite
|
Sign up to set email alerts
|

Musical chairs mortality functions: density-dependent deaths caused by competition for unguarded refuges

Abstract: Structural refuges within which prey can escape from predators can be an important limiting resource for the prey. In a manner that resembles the childhood game of musical chairs, many prey species rapidly retreat to shared, unguarded refuges whenever a predator threatens, and only when refuges are relatively abundant do all prey individuals actually escape. The key feature of this process is that the per capita prey mortality rate depends on the ratio of prey individuals to refuges. We introduce a new class o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…In contrast, a meta-analysis of reef fish studies found strong evidence for density dependence, even in the subset of studies that individually lacked sufficient statistical power to detect it (Osenberg et al 2002). Subsequent work also indicates that density dependence is important in reef fishes, but most such studies have focused on relatively small, siteattached species (e.g., Johnson 2008, Samhouri et al 2009). The fact that our estimates of the strength of density dependence are, if anything, stronger in the roving grazers and scrapers than in the territorial grazers ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a meta-analysis of reef fish studies found strong evidence for density dependence, even in the subset of studies that individually lacked sufficient statistical power to detect it (Osenberg et al 2002). Subsequent work also indicates that density dependence is important in reef fishes, but most such studies have focused on relatively small, siteattached species (e.g., Johnson 2008, Samhouri et al 2009). The fact that our estimates of the strength of density dependence are, if anything, stronger in the roving grazers and scrapers than in the territorial grazers ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1b-c) that continuously accelerate or decelerate (i.e., the second derivative is never equal to zero). Similar piecewise functions have been used widely to identify thresholds for biological effects of contaminants [25], edge effects on ecological communities [26], phase-dependent dynamics in cyclic populations [27], and density-dependent mortality in fish populations [28], to name just a few examples.…”
Section: Methodsmentioning
confidence: 99%
“…Although less conventional than other functions (e.g., Gompertz, von Bertalanffy), the bi-phasic piecewise regression models provide more parsimonious descriptions of various metabolic, energetic, and ecological processes-including growth in fish. This is supported by a growing body of theoretical (Quince et al 2008a) and empirical (Post and Lee 1996;Post and Parkinson 2001;Quince et al 2008b;Samhouri et al 2009) literature. Furthermore, piecewise regression provides a convenient method for calculating the change in growth rate (indicated by the change in slope coefficients) and the age at which growth slows (indicated by the value of the independent variable at slope flexure), thereby allowing us to determine whether the change in growth coincided with an increase in energy allocation to storage (see below: "Energy allocation").…”
Section: Growthmentioning
confidence: 71%